DINAMIKA GENERASI SANDWICH DALAM PENGELOLAAN KEUANGAN : SEBUAH STUDI FENOMENOLOGI - Dewi, Desak Putu Nitya; Putra, Anak Agung Gede Adi Mega; Kusuma, Ni Putu Noviyanti (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2024)
The purpose of this study is to investigate the significance of the sandwich generation's financial management experiences in challenging financial times. Qualitative research design using interpretive phenomenological approach was employed. Three individuals who embodied the sandwich generation were interviewed in-depth in order to gather data. The Interpretative Phenomenological Analysis method was employed to examine the interview results. The findings of this study suggest that the elements that drive informants to fulfill their role as a sandwich generation include favorable attitudes, subjective norms, perceived behavioral control, and felt religiosity. Based on his interpretation of the event, the informant experienced good emotions such as pride and believed that taking on this responsibility was a way of showing his parents love